Direct power control method of maximum power point tracking (MPPT) algorithm for Pico-Hydrokinetic River Energy Conversion System - Wan Ismail, Ibrahim; Raja Mohd Taufika, Raja Ismail; Mohd Rusllim, Mohamed (Springer Singapore, 2020)
In this paper, a design of maximum power point tracking (MPPT) algorithm for the pico-hydrokinetic system in river application has been proposed. The design topology consists of the permanent magnet synchronous generator (PMSG), a three-phase bridge rectifier and a DC boost converter. The proposed MPPT algorithm is a combination of modified hill-climbing search algorithm (MHCS) with the current PI-controller. The MPPT concept is based on measuring the rectifier output voltage and current respectively to produce the reference current (IMPP). The PI-controller has been used to tune the error signal between IMPP and actual inductance current (Idc) to provide the duty-cycle of the boost converter. A comparison is performed between the fixed step HCS and the proposed MPPT to investigate the performance of the algorithm. The results show the proposed algorithm able to harness the maximum power with 96.32% efficiency.